Method for evaluating dissolution of organic matters in anticorrosive coating on inner wall of demineralized water tank

By establishing a model and evaluation model for the dissolution rate of the anticorrosive coating organic matter with the immersion time, the defects of the organic matter dissolution control methods and indicators in the prior art are solved, and the accurate evaluation and effective control of the dissolution of the anticorrosive coating organic matter is achieved, ensuring that the water quality of the water tank effluent meets the requirements.

CN119804570APending Publication Date: 2025-04-11ELECTRIC POWER RESEARCH INSTITUTE OF STATE GRID JIBEI ELECTRIC POWER CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411766714.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art has defects in the dissolution control methods and indicators of organic matter in polyurea anticorrosive coatings, including the lack of systematic analysis and systematic analysis to change the organic matter dissolution rate, unreasonable evaluation methods and poor operability with a long measurement time.

Method used

By establishing a model of the dissolution rate of the anticorrosive coating organic matter changes with the immersion time, the immersion time of the coating test piece to be evaluated is determined, and a test method for determining the organic dissolution rate of the coating test piece and the contribution value evaluation model of the organic matter content to the total organic carbon of the desalinated water is established to achieve an accurate evaluation of the dissolution of the anticorrosive coating organic matter.

Benefits of technology

The accurate description of the dissolution characteristics of the anticorrosion coating organic matter is achieved, the accuracy and operability of evaluation are improved, and the organic solution of the anticorrosion coating on the inner wall of the desalinated water tank of the power plant can be effectively controlled, ensuring that the water effluent organic matter meets the normal production and operation requirements of the generator set.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119804570A_ABST
    Figure CN119804570A_ABST
Patent Text Reader

Abstract

The invention discloses an organic matter dissolution evaluation method for an anti-corrosion coating on the inner wall of a desalted water tank. The method comprises the following steps: determining a relation model between the organic matter dissolution rate and the soaking time in the soaking process of the anticorrosive coating in demineralized water at room temperature; soaking a to-be-evaluated anti-corrosion coating test piece in the demineralized water to obtain a soaking solution; measuring the total organic carbon content in the soaking solution when the soaking time is 7-10 days; calculating the organic matter dissolution rate of the test piece when the soaking time is 7-10 days; calculating the contribution value of the organic matters dissolved out of the coating to the total organic carbon; and evaluating the organic matter dissolution of the anticorrosive coating on the inner wall of the desalted water tank according to the contribution value of the organic matter dissolved out of the coating to the total organic carbon. According to the method, the model that the dissolution rate of the organic matter of the anticorrosive coating changes along with the soaking time is established, the contribution value evaluation model of the content of the dissolved organic matter of the anticorrosive coating to the total organic carbon content of the demineralized water is established, and then the dissolution of the organic matter of the anticorrosive coating can be evaluated more accurately.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for evaluating the dissolution of organic matter from an anti-corrosion coating on the inner wall of a desalted water tank, belonging to the technical field of evaluation of anti-corrosion coatings. Background Art

[0002] The application of organic polymer anti-corrosion coatings such as polyurea sprayed on the inner wall of desalted water tanks in nuclear power plants and thermal power plants is becoming more and more widespread. The dissolution of this polymer organic coating in the desalted water medium has a direct impact on the water quality of the water tank supply. After the inner wall of the desalted water tank of several power plants was completed with anti-corrosion coating and put into operation, the conductivity and total organic carbon content of the water discharged from the water tank exceeded the standard for a long time (for more than half a year), which seriously affected the normal operation of the desalted water tank inner wall after anti-corrosion during the normal production and operation of the generator set, causing great economic losses. The main reason for these problems is the dissolution of the anti-corrosion coating after long-term immersion in desalted water.

[0003] The dissolution of the anti-corrosion coating on the inner wall of the desalting water tank in the desalting water is an important technical indicator that must be considered in addition to the conventional properties of the coating such as anti-corrosion, waterproofing and anti-aging.

[0004] The existing technologies regarding the dissolution characteristics of the anti-corrosion coating on the inner wall of the desalting water tank, the detection of dissolved substances and the impact on water quality are as follows: "Experimental Research and Application of Dissolution Characteristics of Anti-corrosion Coating on the Inner Wall of Desalting Water Tanks in Power Plants" (Xing Chengxia, Li Yongli, et al., Coatings Industry, 2016, 46(1): 63-68.); and "Detection of Dissolution of Polyurea Anti-corrosion Coating in Desalting Water Tanks and Its Impact on Water Quality" (Xing Chengxia, Chen Weiwei, Hu Yuanxiang, et al., Electroplating and Finishing, 2022, 41(18): 1333-1337.).

[0005] In the above-mentioned prior art, a method for detecting the dissolution rate of polyurea anti-corrosion coating in desalted water with total organic carbon (TOC) as the characteristic indicator was established. Polyurea anti-corrosion coating test pieces from several representative manufacturers were selected, and the TOC dissolution law of the test pieces from each manufacturer in desalted water was investigated. The dissolution rate was determined and a comparative analysis was conducted. According to the TOC control value of the desalted water tank water supply of the power plant, the influence of TOC dissolution of polyurea anti-corrosion coating from each manufacturer on the water quality of the water tank water supply was analyzed. The results show that polyurea anti-corrosion coatings all have a certain degree of organic matter dissolution in desalted water, which mainly occurs in the rapid growth period of the initial dissolution stage (1 to 2 weeks). When the dissolution rate is greater than 10μg / (cm 2 After this period, the TOC dissolution rate dropped significantly to less than 2.0 μg / (cm2·d), which had little effect on the water quality of the water tank.

[0006] After years of practical application, it was found that the above-mentioned prior art has the following problems in the control method and index of organic matter dissolution of polyurea coating:

[0007] (1) There is a lack of systematic analysis and research on the variation of the organic matter dissolution rate of the anti-corrosion coating with the immersion time in deionized water for a long time, and no mathematical model has been established for the variation of the organic matter dissolution rate of the coating with the immersion time;

[0008] (2) The proposed evaluation method for organic matter dissolution from anti-corrosion coatings is unreasonable;

[0009] (3) The determination time of organic matter dissolution rate of anti-corrosion coating is long and the operability is poor. Summary of the invention

[0010] In order to solve at least one of the above technical problems, the present invention provides a method for evaluating the dissolution of organic matter from an anti-corrosion coating on the inner wall of a desalted water tank. The present invention establishes a model for the change of the dissolution rate of organic matter from the anti-corrosion coating with the immersion time, determines the immersion time of the anti-corrosion coating specimen to be evaluated in the desalted water, establishes a test method for determining the organic dissolution rate of the coating specimen, and establishes an evaluation model for the contribution of the organic matter content dissolved from the anti-corrosion coating to the total organic carbon content of the desalted water, thereby being able to more accurately evaluate the dissolution of organic matter from the anti-corrosion coating.

[0011] In order to achieve the above object, the present invention provides a method for evaluating the dissolution of organic matter from the anti-corrosion coating on the inner wall of a desalted water tank, which comprises the following steps:

[0012] (1) The relationship model between the organic matter dissolution rate and the immersion time of the anti-corrosion coating in deionized water at room temperature (25±5℃) is as follows:

[0013]

[0014] Where: v is the organic matter dissolution rate, unit is μg / (cm 2 ·d); T is the soaking time in days; k 1 >0;-1.0 <k 2 <0;

[0015] (2) determining that the immersion time of the anti-corrosion coating test piece to be evaluated in the desalted water is one day in the range of 7 to 10 days based on the relationship model between the organic matter dissolution rate and the immersion time in step (1); immersing the anti-corrosion coating test piece to be evaluated in the desalted water to obtain an immersion solution; and determining the total organic carbon content in the immersion solution when the immersion time is one day in the range of 7 to 10 days;

[0016] (3) The organic matter dissolution rate of the test piece when the immersion time is one day between 7 and 10 days is calculated using the following formula:

[0017]

[0018] Where: v is the organic matter dissolution rate of the test piece when the immersion time is t days, the unit is μg / (cm 2 ·d); C t is the total organic carbon content in the soaking solution when the soaking time is t days obtained in step (2), in mg / L; s is the surface area of ​​the test piece, in cm 2 ; t is the soaking time, which is 7 to 10 days; V is the volume of the soaking solution, in mL;

[0019] (4) The following formula is used to calculate the contribution of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalted water tank to the total organic carbon content of the desalted water under ideal conditions:

[0020]

[0021] Among them: The ideal situation refers to the organic matter of the anti-corrosion coating on the inner wall of the desalted water tank being uniformly dissolved and uniformly diffused in the desalted water; ΔC 理 is the contribution of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalting water tank to the total organic carbon content of the desalting water under ideal conditions, in μg / L; v is the organic matter dissolution rate of the test piece when the immersion time is one day among 7 to 10 days obtained in step (3), in μg / (cm 2 ·d); S is the inner surface area of ​​the desalted water tank, which is the sum of the side area and the bottom area, in cm 2 ;Q 额定 is the steam evaporation capacity of the generator set under rated conditions, in t / h; δ is the water replenishment rate during normal operation of the generator set, without unit; 24 is the water supply time of the desalted water tank under rated conditions of the generator set, calculated as 24 hours; 1000 is the volume conversion coefficient;

[0022] (5) Based on the contribution value of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalting water tank to the total organic carbon content of the desalting water obtained in step (4) under ideal conditions, the dissolution of organic matter from the anti-corrosion coating on the inner wall of the desalting water tank is evaluated.

[0023] According to a specific embodiment of the present invention, preferably, in step (2), the ratio of the surface area of ​​the anti-corrosion coating specimen to be evaluated to the volume of the immersion liquid (i.e., the surface-to-volume ratio) is (0.1-0.3) cm -1 Based on the surface-to-volume ratio, the number, size, and volume of the test pieces can be adjusted as long as the surface-to-volume ratio range is met. If multiple test pieces are used, the surface area of ​​the test piece is the total surface area of ​​all the test pieces.

[0024] According to a specific embodiment of the present invention, preferably, in step (2), the preparation steps of the anti-corrosion coating specimen to be evaluated include: spraying the coating on the surface of the template to form a coating; curing the coating for 24 hours after formation, and then demolding without using a release agent to obtain a demolded coating; curing the demolded coating for more than 30 days to obtain the anti-corrosion coating specimen to be evaluated.

[0025] According to a specific embodiment of the present invention, preferably, the desalted water is ultrapure water, and its resistivity is 18.2 MΩ.

[0026] According to a specific embodiment of the present invention, preferably, in step (2), the soaking temperature is room temperature (25±5° C.).

[0027] According to a specific embodiment of the present invention, preferably, in step (2), the total organic carbon content in the soaking liquid can be determined according to the total organic carbon content determination method described in ASTM D5904-2009 "Test method for total carbon content, organic carbon and inorganic carbon in water by ultraviolet light, persulfate oxidation and thin film conductivity detection", or it can be determined by other methods such as spectrophotometry.

[0028] According to a specific embodiment of the present invention, preferably, in step (5), if the contribution value of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalted water tank to the total organic carbon content of the desalted water tank is less than or equal to the control value of the organic matter content in the desalted water tank water supply under ideal conditions, then the organic matter dissolution of the anti-corrosion coating is qualified; if the contribution value of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalted water tank to the total organic carbon content of the desalted water tank is greater than the control value of the organic matter content in the desalted water tank water supply under ideal conditions, then the organic matter dissolution of the anti-corrosion coating is unqualified. The control value of the organic matter content in the desalted water tank water supply is determined based on relevant standards or power plant requirements.

[0029] According to a specific embodiment of the present invention, preferably, step (5) further comprises: evaluating the dissolution of organic matter from the anti-corrosion coating on the inner wall of the desalting water tank according to the organic matter dissolution rate of the test piece when the immersion time is one day among 7 to 10 days obtained in step (3) and the contribution value of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalting water tank to the total organic carbon content of the desalting water obtained in step (4) under ideal conditions; if the organic matter dissolution rate of the test piece when the immersion time is one day among 7 to 10 days is less than 0.5 μg / (cm 2 ·d), and ideally, the contribution of the organic matter dissolved from the anti-corrosion coating on the inner wall of the desalting water tank to the total organic carbon content of the desalting water is less than or equal to the control value of the organic matter content in the desalting water tank supply water. In this case, the impact of the organic matter dissolved from the anti-corrosion coating on the water quality of the desalting water tank has been minimized.

[0030] The present invention has at least the following beneficial effects:

[0031] The present invention proposes an evaluation method for the dissolution of organic matter in the anti-corrosion coating on the inner wall of a desalted water tank. By establishing a decay change model of the dissolution rate of organic matter in the anti-corrosion coating with immersion time, the dissolution characteristics of organic matter in the anti-corrosion coating in desalted water are obtained; by establishing a test method for determining the organic dissolution rate of coating specimens and an evaluation model for the contribution of the organic matter content dissolved from the coating to the total organic carbon of the desalted water, the effect of the dissolution of organic matter in the anti-corrosion coating on the water quality of the desalted water can be accurately evaluated; and based on the evaluation results of the present invention, the organic dissolution of the anti-corrosion coating on the inner wall of the desalted water tank of a power plant can be effectively controlled to ensure that the organic matter in the water outlet of the water tank meets the normal production and operation requirements of the generator set. In addition, the present invention has strong operability, does not require excessively long measurement time, and has high rationality and reliability of the evaluation model. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the curve of total organic carbon dissolution of S-5 specimen changing with immersion time.

[0033] Figure 2 This is the curve of organic matter dissolution rate of S-5 specimen changing with immersion time.

[0034] Figure 3 This is the curve of organic matter dissolution rate of B-4 specimen changing with immersion time.

[0035] Figure 4 This is the curve of organic matter dissolution rate of S-3 specimen changing with immersion time.

[0036] Figure 5 This is the curve of organic matter dissolution rate of Q-1 specimen changing with immersion time.

[0037] Figure 6 This is the curve of organic matter dissolution rate of W-1 specimen changing with immersion time.

[0038] Figure 7 This is the curve of organic matter dissolution rate of H-1 specimen changing with immersion time.

[0039] Figure 8 This is the on-site monitoring and analysis results of the effluent quality in the first year after the desalination water tank of a power plant was put into operation.

[0040] Fig. 9 This is the curve showing the change of organic matter dissolution rate of the anti-corrosion coating specimen on the inner wall of a desalting water tank in a power plant as a function of immersion time. DETAILED DESCRIPTION

[0041] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the present invention is now described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.

[0042] It should be noted that, unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs.

[0043] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0044] It should be understood that the terms "comprises," "comprising" and / or "containing" when used herein specify the presence of stated features, integers, steps, components or combinations thereof, but do not preclude the presence or addition of one or more other features, integers, steps, components or combinations thereof.

[0045] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0046] The present invention provides a method for evaluating the dissolution of organic matter from an anti-corrosion coating on the inner wall of a desalting water tank. The method first proposes an attenuation change model in which the organic matter dissolution rate of the anti-corrosion coating on the inner wall of a desalting water tank is in a process of long-term immersion in desalting water at room temperature (25±5°C), and the organic matter dissolution rate of the anti-corrosion coating is in a negative power function relationship with the immersion time. On this basis, a method for evaluating the dissolution of organic matter from the anti-corrosion coating on the inner wall of a desalting water tank is provided.

[0047] According to a specific embodiment of the present invention, the present invention provides a method for evaluating the dissolution of organic matter from the anti-corrosion coating on the inner wall of a desalted water tank, which comprises the following steps:

[0048] (1) The relationship model between the organic matter dissolution rate and the immersion time of the anti-corrosion coating in deionized water at room temperature (25±5℃) is as follows:

[0049]

[0050] Where: v is the organic matter dissolution rate, unit is μg / (cm 2 ·d); T is the soaking time in days; k 1 >0;-1.0 <k 2 <0;

[0051] (2) determining that the immersion time of the anti-corrosion coating test piece to be evaluated in the desalted water is one day in the range of 7 to 10 days based on the relationship model between the organic matter dissolution rate and the immersion time in step (1); immersing the anti-corrosion coating test piece to be evaluated in the desalted water to obtain an immersion solution; and determining the total organic carbon content in the immersion solution when the immersion time is one day in the range of 7 to 10 days;

[0052] (3) The organic matter dissolution rate of the test piece when the immersion time is one day between 7 and 10 days is calculated using the following formula:

[0053]

[0054] Where: v is the organic matter dissolution rate of the test piece when the immersion time is t days, the unit is μg / (cm 2 ·d); C t is the total organic carbon content in the soaking solution when the soaking time is t days obtained in step (2), in mg / L; s is the surface area of ​​the test piece, in cm 2 ; t is the soaking time, which is 7 to 10 days; V is the volume of the soaking solution, in mL;

[0055] (4) The following formula is used to calculate the contribution of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalted water tank to the total organic carbon content of the desalted water under ideal conditions:

[0056]

[0057] Among them: The ideal situation refers to the organic matter of the anti-corrosion coating on the inner wall of the desalted water tank being uniformly dissolved and uniformly diffused in the desalted water; ΔC 理 is the contribution of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalting water tank to the total organic carbon content of the desalting water under ideal conditions, in μg / L; v is the organic matter dissolution rate of the test piece when the immersion time is one day among 7 to 10 days obtained in step (3), in μg / (cm 2 ·d); S is the inner surface area of ​​the desalted water tank, which is the sum of the side area and the bottom area, in cm 2 ;Q 额定 is the steam evaporation capacity of the generator set under rated conditions, in t / h; δ is the water replenishment rate during normal operation of the generator set, without unit; 24 is the water supply time of the desalted water tank under rated conditions of the generator set, calculated as 24 hours; 1000 is the volume conversion coefficient;

[0058] (5) Based on the contribution value of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalting water tank to the total organic carbon content of the desalting water obtained in step (4) under ideal conditions, the dissolution of organic matter from the anti-corrosion coating on the inner wall of the desalting water tank is evaluated.

[0059] In step (5), if the contribution value of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalted water tank to the total organic carbon content of the desalted water tank is less than or equal to the control value of the organic matter content in the desalted water tank water supply under ideal conditions, the organic matter dissolution of the anti-corrosion coating is qualified; if the contribution value of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalted water tank to the total organic carbon content of the desalted water tank is greater than the control value of the organic matter content in the desalted water tank water supply under ideal conditions, the organic matter dissolution of the anti-corrosion coating is unqualified. The control value of the organic matter content in the desalted water tank water supply is determined based on relevant standards or power plant requirements.

[0060] Step (5) further comprises: evaluating the dissolution of organic matter from the anti-corrosion coating on the inner wall of the desalting water tank according to the organic matter dissolution rate of the test piece when the immersion time is one day among 7 to 10 days obtained in step (3) and the contribution value of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalting water tank to the total organic carbon content of the desalting water obtained in step (4) under ideal conditions; if the organic matter dissolution rate of the test piece when the immersion time is one day among 7 to 10 days is less than 0.5 μg / (cm 2 ·d), and ideally, the contribution of the organic matter dissolved from the anti-corrosion coating on the inner wall of the desalting water tank to the total organic carbon content of the desalting water is less than or equal to the control value of the organic matter content in the desalting water tank supply water. In this case, the impact of the organic matter dissolved from the anti-corrosion coating on the water quality of the desalting water tank has been minimized.

[0061] 1. Construction of organic matter dissolution rate model for anti-corrosion coating

[0062] It is determined that the organic matter dissolution rate (v) of the anti-corrosion coating during immersion in desalted water at room temperature decays with the immersion time (T) in a negative power function relationship. The relationship model between the two is as follows:

[0063] f(v)=k 1 ×T k2

[0064] Where: k 1 and k 2 is a constant, k 1 >0, -1.0 <k 2 <0;

[0065] k 1 It is mainly affected by the total amount of soluble matter in the coating, that is, the greater the content of easily soluble matter added to the coating raw material, the greater the k 1 The larger it is, the longer the impact period on the water quality of the desalted water tank will be.

[0066] k 2 It is mainly affected by factors such as the physical and mechanical properties of the coating itself, the density of the coating and the environment.

[0067] (1) Preparation of test pieces and immersion solution

[0068] Preparation of test piece: spray the coating on the surface of the template to form a coating; after the coating is formed, cure for 24 hours, then demould without using a release agent to obtain a demoulded coating; cure the demoulded coating for more than 30 days to obtain a test piece. Specifically, the template used should be flat, clean and smooth. In addition, the role of not using a release agent is to prevent additional organic contamination of the coating. The curing conditions are: room temperature (25±5℃).

[0069] The size and quantity of the test piece: depends on the ratio of the surface area of ​​the test piece to the volume of the immersion liquid, that is, the surface-to-volume ratio. The surface-to-volume ratio can be controlled within (0.1-0.3) cm -1 Clean the surface of the test piece, dry it, and weigh it for later use.

[0070] Preparation of soaking solution: prepare 2 glass reagent bottles of appropriate capacity, wash them to ensure that the sampling bottles are clean and free of contamination. Pour an appropriate amount of deionized water into the bottles according to the set surface-to-volume ratio, cover the bottles and let them stand at room temperature (25±5℃).

[0071] (2) Determination of organic matter dissolution rate of test piece

[0072] Determination index: Total organic carbon (TOC) content

[0073] Determination method: It can be determined by the method described in ASTM D5904-2009 "Test method for total carbon, organic carbon, and inorganic carbon in water by ultraviolet light, persulfate oxidation, and thin film conductivity detection", or by other determination methods such as spectrophotometry.

[0074] Test time interval: The sampling test time interval is the 1st, 3rd, 5th and 7th day after the test piece is soaked. Then adjust the test time interval appropriately according to the TOC content and change trend in the soaking solution. Determine the final soaking time according to the change law of TOC content in the soaking solution. The soaking time of the test piece in this test is 30d to 50d. After each sampling and measurement, add the same sampling volume of deionized water to the bottle to keep the total volume of the test piece soaking solution unchanged.

[0075] The organic matter dissolution rate at each measuring point is calculated as follows:

[0076]

[0077] in:

[0078] i: is the number of sampling measurements.

[0079] v i : The organic matter dissolution rate of the ith time, unit: μg / (cm 2 d);

[0080] C1 , C 2 ,……,C i-1 , C i : TOC content value of each sampling test, unit: mg / L;

[0081] V t : The sampling volume for each sampling measurement, unit: mL;

[0082] V p : is the total volume of the soaking solution, unit: mL;

[0083] S: Surface area of ​​the test piece, unit: cm 2 ;

[0084] T i : is the immersion time of the test piece during the i-th sampling measurement, in days (d).

[0085] With the immersion time (days) as the horizontal axis and the TOC content in the immersion solution and the organic matter dissolution rate as the vertical axis, the curves of the total organic carbon dissolution amount and the organic matter dissolution rate of the test piece changing with the immersion time were plotted.

[0086] Taking the polyurea coating specimen numbered S-5 as an example, the curves of the total organic carbon dissolution amount and organic matter dissolution rate of the specimen with immersion time are as follows: Figure 1 and Figure 2 shown.

[0087] The dissolution rate of organic matter in various types of anti-corrosion coating specimens was measured as a function of immersion time. Figures 3 to 7 .

[0088] Based on the above results, it can be seen that the relationship model between the dissolution rate of organic matter in the anti-corrosion coating and the immersion time of the present invention is consistent with the variation curves of the dissolution rate of organic matter in the above-mentioned various types of anti-corrosion coating test pieces with the immersion time, and has high accuracy.

[0089] The immersion dissolution test data of representative coating specimens for corrosion protection of the inner wall of 6 different types of desalted water tanks were analyzed, and the proportion of total organic carbon dissolution in the initial dissolution stage of the coating to the total dissolution during the entire coating immersion period was calculated. The results are shown in Table 1.

[0090] Table 1 Calculation results of the proportion of organic matter dissolved in the initial dissolution stage of the coating

[0091]

[0092]

[0093] It can be seen that 55% to 71% of the soluble organic matter in these coating test pieces was dissolved in the initial dissolution stage. Therefore, combined with the attenuation model of the coating dissolution rate changing with the immersion time, the initial dissolution rate of the coating determines the level of organic matter dissolution of the coating. The initial dissolution rate of the coating can be used as an evaluation index for the dissolution of organic matter in the coating, and there is no need to conduct a deep dissolution test.

[0094] According to the coating organic matter dissolution rate attenuation model curve, when the coating is immersed for 7 to 15 days, the dissolution rate decline trend begins to slow down, and the coating enters the deep slow release dissolution stage. The proportion of the dissolution amount of the coating immersed for 7 and 15 days to the dissolution amount of the entire initial stage was calculated, and the calculation results are shown in Table 2.

[0095] Table 2 Calculation results of the percentage of dissolution amount on the 7th and 15th days of the initial dissolution stage of the coating

[0096]

[0097] It can be seen that except for the test piece numbered B-4 which basically stopped dissolving after reaching equilibrium on the 7th day (accounting for 90.9%), the dissolution amount of other test pieces on the 7th day accounted for 32% to 48% of the total dissolution amount, and the dissolution amount on the 15th day accounted for 48% to 72% of the total dissolution amount. It can be seen that 30% to 70% of the organic matter dissolution amount in the initial dissolution stage of the coating occurs on the 7th to 15th day of the initial dissolution stage of the coating.

[0098] The dissolution rate of the test piece shows a negative power function attenuation trend with the immersion time. When the immersion time reaches 7 to 10 days, the organic matter dissolution of the test piece reaches 30% to 60% of the total dissolution amount during the entire immersion period, and the dissolution rate in this stage decreases rapidly and linearly. Then, as the immersion time increases, the dissolution of the test piece gradually decreases, and the trend of the dissolution rate decreases slowly. That is, when the immersion time is 7 to 10 days, the proportion of organic matter dissolution of the test piece reaches 30% to 60%, and the dissolution rate decays rapidly; when the immersion time of the test piece exceeds 7 to 10, the organic matter dissolution is characterized by slow release dissolution, and the dissolution rate is small and changes slowly.

[0099] 2. Evaluation method for dissolution of organic matter from the anti-corrosion coating on the inner wall of the desalination tank

[0100] First, as a comparison, the coating organic matter dissolution test methods in two prior art documents in the background technology were used to measure the organic matter dissolution characteristics and dissolution rate of the anti-corrosion coating samples on the inner wall of a power plant's desalting water tank. The inner wall of the power plant's desalting water tank was anti-corrosive using a special type of polyurea coating for the inner wall of the power plant's desalting water tank. After the project construction was accepted, the water tank was filled with water and flushed before being put into operation. It was found that the conductivity and TOC content of the water outlet from the water tank exceeded the standard. After one year of repeated soaking and flushing, the conductivity and TOC of the water outlet from the water tank basically met the control requirements. The specific test results are as follows Figure 8 and Fig. 9 shown.

[0101] Figure 8 This is the result of on-site monitoring and analysis of the effluent quality in the first year after the desalting water tank of the power plant was put into operation. It can be seen that during the nearly one year of full water immersion and flushing of the water tank, the online conductivity and TOC content of the effluent fluctuated and gradually decreased. The initial maximum conductivity value (November 11, 2022) was 1.708μS / cm, and it dropped to less than 0.2μS / cm after one year, and reached a stable control level. The TOC content in the corresponding water sample dropped from 1730μg / L to below 100μg / L, reaching the qualified level.

[0102] During this period, the water tank inner wall coating sample (numbered B-1) of the power plant was subjected to organic matter dissolution immersion test. The test results are as follows: Fig. 9 shown. Fig. 9 In the figure, the main coordinates (the horizontal coordinate below and the vertical coordinate on the left) are the relationship between the dissolution rate in the initial dissolution stage and the immersion time. The total immersion time is 47 days, and the initial dissolution rate (equilibrium time is 7 to 10 days) is 23.57 μg / (cm 2 d), k in the power function relationship 1 The value is as high as 80.37. It can be seen that the content of easily soluble organic matter in the coating test piece is relatively large.

[0103] In the following nearly one year, five deep dissolution tests were carried out. Fig. 9 The middle coordinates (the upper horizontal axis and the right vertical axis) are the relationship between the dissolution rate and the immersion time in the deep dissolution stage. The deep dissolution rate (equilibrium time is 20 days) increases from 3.10 μg / (cm 2 d) decreased to 0.87 μg / (cm 2 ·d), the total immersion time is 480 days.

[0104] The results of the test piece organic matter dissolution rate were analyzed in correspondence with the actual TOC test results of the water tank. It can be seen that the first deep dissolution rate of the test piece is greater than 2.0μg / (cm 2 ·d), the conductivity and TOC content of the water discharged from the water tank still exceeded the standard. Until the fifth deep dissolution stage, the dissolution rate was less than 1.0μg / (cm 2 ·d), the water quality of the corresponding water tank is basically qualified.

[0105] It can be seen that when the initial dissolution rate of the coating specimen (during the equilibrium time) is greater than 10 μg / (cm 2·d), the impact on water quality is greater. However, when entering the deep dissolution stage, it cannot be guaranteed that there will be no impact on water quality. The greater the initial dissolution rate of the coating, the greater the deep dissolution rate of the coating when the organic matter is slowly released in the later stage, and the longer the impact period on water quality.

[0106] According to the test results of this embodiment, combined with the current desalination tank inner wall anticorrosive coating organic matter dissolution level (see Figures 2 to 7 ), the organic matter dissolution rate of the anti-corrosion coating after immersion in deionized water for 7 to 10 days is less than 0.5 μg / (cm 2 ·d) can minimize the impact of coating organic matter dissolution on water quality.

[0107] After the anti-corrosion coating is sprayed on the inner wall of the desalted water tank of the power plant, after a period of coating stabilization, water is injected and flushed. When the effluent meets the water quality requirements, the water tank can be put into operation to supply water to the unit. The time for water injection and flushing of the desalted water tank is determined by the level of organic matter dissolution of the coating on the inner wall of the water tank. The smaller the dissolution rate of organic matter in the coating, the less time the water tank is flushed, which is more conducive to water saving and engineering quality evaluation. The flushing time before the water tank is put into operation is controlled within 7 to 10 days, which is acceptable for power plants. This time is consistent with the law and characteristics of the change of organic matter dissolution rate of the coating in the desalted water for a long time. In addition, during the normal operation of the water tank, due to the influence of various water supply factors, the maximum residence time of the desalted water in the water tank is usually no more than 7 to 10 days. Therefore, the test time of the coating organic matter dissolution evaluation test is controlled within 7 to 10 days.

[0108] Based on the coating organic matter dissolution characteristic model, actual sample immersion test data analysis, and the actual operating characteristics and water quality control requirements of the desalting water tank in the power plant, the organic matter dissolution evaluation method of the anti-corrosion coating on the inner wall of the desalting water tank of the present invention was established, and the accuracy and rationality of the method of the present invention were verified through the above content.

[0109] Example

[0110] This embodiment provides a method for evaluating the dissolution of organic matter from an anti-corrosion coating test piece on the inner wall of a desalted water tank in a power plant.

[0111] Test piece preparation:

[0112] (1) Preparation of test pieces and immersion solution

[0113] Test piece preparation: According to the ratio and parameter requirements of the polyurea raw material, use special spraying equipment to spray the polyurea raw material on the template. The template should be flat, clean and smooth, and no release agent should be used to prevent additional organic pollution to the coating. After the coating is formed, it should be demoulded after curing for 24 hours. After demoulding, continue to cure for at least 30 days before conducting the dissolution immersion test.

[0114] The size and quantity of the test pieces are shown in Table 3.

[0115] Table 3S-3 Test piece dimensions and quantity

[0116]

[0117] Clean the surface of the test piece, dry it, weigh it and set it aside.

[0118] Preparation of soaking solution: Prepare two 500mL glass reagent bottles and wash them to ensure that the sampling bottles are clean and free of contamination. Pour 500mL of deionized water into each bottle. It is ultrapure water for laboratory use with a resistivity of 18.2MΩ. After calculation, the surface-to-volume ratio is 0.15cm -1 Cover the bottle and let it stand at room temperature (25±5℃).

[0119] (2) Determination of organic matter dissolution rate of test piece

[0120] Determination index: Total organic carbon (TOC) content

[0121] Determination method: The method described in ASTM D5904-2009 "Test method for total carbon, organic carbon, and inorganic carbon in water by ultraviolet light, persulfate oxidation, and thin film conductivity detection" was adopted.

[0122] The results of the test are as follows Figure 4 When the coating was immersed for 7 days, the dissolution rate showed an inflection point as a function of immersion time, and its attenuation rate began to decrease.

[0123] If S-3 coating is used in a 3600t desalted water tank (surface volume ratio is 0.29) of a 600MW generator set, Q 额定 Based on 2000t / h and the water replenishment rate δ of 1.0% during normal operation of the unit, calculate the contribution of organic matter dissolution of the coating to the total organic carbon content of the desalted water in the water tank under ideal conditions.

[0124] The results of this example are as follows: when the immersion time is 7 days, the dissolution rate of organic matter in the coating is 1.08 μg / (cm 2 ·d) Ideally, the contribution of coating organic matter dissolution to the total organic carbon content of the desalted water in the water tank is 24.52 μg / L.

[0125] Based on the organic matter dissolution rate of the test piece when the immersion time is 7 days and the contribution of the coating organic matter dissolution to the total organic carbon content of the desalted water, it can be concluded that the organic matter dissolution rate of the test piece when the immersion time is 7 days is 1.08μg / (cm 2·d), and the contribution of the coating organic matter dissolved into the total organic carbon content in the desalted water of the water tank was 24.52μg / L, which did not exceed the TOC control value of the 600MW unit for the desalted water tank supply water (less than 50μg / L), and the coating dissolution level was evaluated as qualified.

[0126] Using the above method, Figure 2 , Figure 3 , Figure 5 , Figure 6 , Figure 7 as well as Fig. 9 The organic matter elution of the coating test pieces with the numbers shown was evaluated. Fig. 9 The test piece numbered B-1 is an actual sample of the anti-corrosion coating on the inner wall of a desalted water tank in a power plant. If the TOC control value in the desalted water tank water supply is less than 50μg / L, the evaluation results are shown in Table 4.

[0127] Table 4 Evaluation results of organic matter dissolution of different types of coating specimens

[0128]

[0129]

[0130] It can be seen that the contribution value of S-3 test piece is the lowest, and the dissolution rate is 1.08 μg / (cm 2 ·d), the contribution value was 23.52μg / L. The higher the dissolution rate, the higher the contribution value, and the longer the impact period on water quality will be. The contribution value of the B-1 test piece reached 513.4μg / L, and the water quality reached the control value one year after the actual water tank was put into operation.

Claims

1. A method for evaluating the dissolution of organic matter from the anti-corrosion coating on the inner wall of a desalted water tank, comprising the following steps: (1) The relationship model between the organic matter dissolution rate and the immersion time of the anti-corrosion coating during immersion in deionized water at room temperature is as follows: Where: v is the organic matter dissolution rate, unit is μg / (cm 2 ·d); T is the soaking time in days; k1>0; -1.0 <k2<0; (2) determining that the immersion time of the anti-corrosion coating test piece to be evaluated in the desalted water is one day in the range of 7 to 10 days based on the relationship model between the organic matter dissolution rate and the immersion time in step (1); immersing the anti-corrosion coating test piece to be evaluated in the desalted water to obtain an immersion solution; and determining the total organic carbon content in the immersion solution when the immersion time is one day in the range of 7 to 10 days; (3) The organic matter dissolution rate of the test piece when the immersion time is one day between 7 and 10 days is calculated using the following formula: Where: v is the organic matter dissolution rate of the test piece when the immersion time is t days, the unit is μg / (cm 2 ·d); C t is the total organic carbon content in the soaking solution when the soaking time is t days obtained in step (2), in mg / L; s is the surface area of ​​the test piece, in cm 2 ; t is the soaking time, which is 7 to 10 days; V is the volume of the soaking solution, in mL; (4) The following formula is used to calculate the contribution of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalted water tank to the total organic carbon content of the desalted water under ideal conditions: Among them: the ideal situation refers to the organic matter of the anti-corrosion coating on the inner wall of the desalted water tank being uniformly dissolved and uniformly diffused in the desalted water; ΔC 理 is the contribution of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalting water tank to the total organic carbon content of the desalting water under ideal conditions, in μg / L; v is the organic matter dissolution rate of the test piece when the immersion time is one day among 7 to 10 days obtained in step (3), in μg / (cm 2 ·d); S is the inner surface area of ​​the desalted water tank, which is the sum of the side area and the bottom area, in cm 2 ;Q 额定 is the steam evaporation capacity of the generator set under rated conditions, in t / h; δ is the water replenishment rate during normal operation of the generator set, without unit; 24 is the water supply time of the desalted water tank under rated conditions of the generator set, calculated as 24 hours; 1000 is the volume conversion coefficient; (5) Based on the contribution value of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalting water tank to the total organic carbon content of the desalting water obtained in step (4) under ideal conditions, the dissolution of organic matter from the anti-corrosion coating on the inner wall of the desalting water tank is evaluated.

2. The method for evaluating the dissolution of organic matter from the anti-corrosion coating on the inner wall of a desalted water tank according to claim 1, wherein: In step (2), the ratio of the surface area of ​​the anticorrosive coating specimen to be evaluated to the volume of the immersion liquid is (0.1-0.3) cm -1 .

3. The method for evaluating the dissolution of organic matter from the anti-corrosion coating on the inner wall of a desalted water tank according to claim 1, wherein: In step (2), the preparation steps of the anti-corrosion coating specimen to be evaluated include: spraying the coating on the surface of the template to form a coating; curing the coating for 24 hours after the coating is formed, and then demolding without using a release agent to obtain a demolded coating; curing the demolded coating for more than 30 days to obtain the anti-corrosion coating specimen to be evaluated.

4. The method for evaluating the dissolution of organic matter from the anti-corrosion coating on the inner wall of a desalted water tank according to claim 1, wherein: The desalted water is ultrapure water, and its resistivity is 18.2 MΩ.

5. The method for evaluating the dissolution of organic matter from the anti-corrosion coating on the inner wall of a desalted water tank according to claim 1, wherein: In step (2), the soaking temperature is room temperature.

6. The method for evaluating the dissolution of organic matter from the anti-corrosion coating on the inner wall of a desalted water tank according to claim 1, wherein: In step (5), if, under ideal circumstances, the contribution value of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalting water tank to the total organic carbon content of the desalting water is less than or equal to the control value of the organic matter content in the desalting water tank supply water, then the organic matter dissolution condition of the anti-corrosion coating is qualified; if, under ideal circumstances, the contribution value of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalting water tank to the total organic carbon content of the desalting water tank is greater than the control value of the organic matter content in the desalting water tank supply water, then the organic matter dissolution condition of the anti-corrosion coating is unqualified.

7. The method for evaluating the dissolution of organic matter from the anti-corrosion coating on the inner wall of a desalted water tank according to claim 1, wherein: Step (5) further comprises: evaluating the dissolution of organic matter from the anti-corrosion coating on the inner wall of the desalting water tank according to the organic matter dissolution rate of the test piece when the immersion time is one day among 7 to 10 days obtained in step (3) and the contribution value of the organic matter content dissolved from the anti-corrosion coating on the inner wall of the desalting water tank to the total organic carbon content of the desalting water obtained in step (4) under ideal conditions; if the organic matter dissolution rate of the test piece when the immersion time is one day among 7 to 10 days is less than 0.5 μg / (cm 2 ·d), and ideally, the contribution of the organic matter dissolved from the anti-corrosion coating on the inner wall of the desalting water tank to the total organic carbon content of the desalting water is less than or equal to the control value of the organic matter content in the desalting water tank supply water. In this case, the impact of the organic matter dissolved from the anti-corrosion coating on the water quality of the desalting water tank has been minimized.